Indra’s Net Life Community and the Ecological Thought of Tobŏp (道法) - Hyung Kyu Lee (Religions)
This study primarily aims to articulate and analyze the Engaged Buddhism movement’s Indra’s Net Life Community in Korea and the ecological thoughts of its founder, Tobŏp. This study examines Reverend Tobŏp’s ideas, which form the foundation and drive the operations of the community. These ideas are informed by the Hua-yen worldview, expressed in the doctrine of “interdependent co-arising,” as put forth in his writings. This movement offers a new ecological vision beyond today’s neoliberal economic model. This study also suggests that ecologically Engaged Korean Buddhism can provide empowering religious teachings with important suggestions for how religio-ethical values might address contemporary ecological problems. Indra’s Net Life Community has the potential to address the shortcomings in most environmental ethics proposals, which often overlook the importance of “practical participatory projects” to promote ecological justice. Finally, this study argues that the focal point of Buddhist enlightenment is “in this place and in this body, in this world and not some other.” Venerable Tobŏp also emphasizes the present situation through the experience of “the here and now.” However, Indra’s Net and Engaged Buddhism are still works in progress.